2014
DOI: 10.1038/nature13039
|View full text |Cite
|
Sign up to set email alerts
|

Protein-guided RNA dynamics during early ribosome assembly

Abstract: The assembly of 30S ribosomes requires the precise addition of 20 proteins to the 16S ribosomal RNA. How early binding proteins change the rRNA structure so that later proteins may join the complex is poorly understood. Here we use single molecule fluorescence resonance energy transfer (smFRET) to observe real-time encounters between ribosomal protein S4 and the 16S 5′ domain RNA at an early stage of 30S assembly. Dynamic initial S4-RNA complexes pass through a stable non-native intermediate before converting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(157 citation statements)
references
References 61 publications
7
141
2
Order By: Relevance
“…Protein structures are dynamic; and conformational dynamics is crucial in many biomolecular interactions [171,172]. Even for globular proteins that fold to an essentially unique native structure under physiological conditions, other less favourable 'excited-state' conformations are always populated, albeit to a much lesser extent than the dominant native conformation that is commonly identified as the ground-state structure.…”
Section: Multi-basin Folding Landscapes Allostery and Conformationalmentioning
confidence: 99%
“…Protein structures are dynamic; and conformational dynamics is crucial in many biomolecular interactions [171,172]. Even for globular proteins that fold to an essentially unique native structure under physiological conditions, other less favourable 'excited-state' conformations are always populated, albeit to a much lesser extent than the dominant native conformation that is commonly identified as the ground-state structure.…”
Section: Multi-basin Folding Landscapes Allostery and Conformationalmentioning
confidence: 99%
“…1A; Stern et al 1986;Gerstner et al 2001;Bellur and Woodson 2009) and nucleates in vitro assembly of the 5 ′ and central domains (Nowotny and Nierhaus 1988). Time-resolved footprinting and smFRET experiments showed that S4 binding induces a series of conformational changes in the 5WJ, leading to the native S4-rRNA complex (Mayerle et al 2011;Kim et al 2014). Remarkably, S4 binding also stabilizes tertiary interactions throughout the 5 ′ -domain RNA, which includes interactions as much as 60 Å away from the S4 binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Previous smFRET experiments in which the 5 ′ -domain RNA was tethered to a microscope slide showed that higher Mg 2+ concentrations favor the docked (native) complex (Kim et al 2014). These experiments only counted long-lived complexes that could be captured on the slide.…”
Section: Mg 2+ Ions Stabilize the Native S4 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these proteins, especially SF3b49 and SF3b145, can possibly act as RNA chaperones 96,97 for the U12 snRNA to take up the right tertiary structure, analogous to that observed in the case of ribosomal proteins for rRNA. [98][99][100] Earlier, extensive mutational and deletion analysis of the SLI (14-17 nucleotides) and single stranded linker region (24-31 nucleotides) of U12 snRNA have shown that they affect splicing. So these regions have been implicated to be spacer elements or distance constraints in the functional form of U12 snRNA, such as during its interaction with pre-mRNA.…”
Section: Sf3b -A Fuzzy Complexmentioning
confidence: 99%